La (re)construction du père chez Annie Ernaux (La Place) et Assia Djebar (Nulle part dans la maison de mon père) - Kotowska, Katarzyna (Romanica Silesiana)
Annie’s Ernaux’ A Man’s Place and Assia Djebar’s Nowhere in My Father’s House can be described as accounts of what separates fathers from daughters in the context of generational and class divisions. Ernaux connects the story of her father’s life and death with the one of herself. Djebar returns to the late colonial period and gives a description of complex transcultural experiences. In both books, the authors employ a special literary form which is referred to as récit de filiation by D. Viart. The reconstruction of the Father is directly linked with the reflection on the processes of writing, the sense of literature, and the necessity of rejection of the fathers’ heritage.